Disproportions in the investment sphere and spatial-economic imbalance in Russia: a political-economic analysis - Rinas Kashbrasiev; Anatoly Trofimov; Roman Elizarov (European Regional Science Association (ERSA), 2002)
Since the beginning of the twentieth century processes of centralization of economic and political power into the hands of the 'nomenklatura' have been taking place in Russia while in the Western capitalist countries the process of decentralization of power has accompanied economic development. The centralization of power during the Soviet period led to the deformation of horizontal and the strengthening of vertical relations, which today still determines the imbalanced economic development of Russia. One of the main characteristics of the deformation processes that have been taking place in the economy is the redistribution of investment resources in favour of the largest economic and political centers in Russia. The aim of this research is to show which of the following features are the main indicators of centralization of investment resources: The formation of polarized structure of society (very small stratum of middle-class representatives), the formation of extremely imbalanced banking sector: Moscow financial-industrial groups play the key role, while the regional financial institutions are very weak, Development of Russian regions is primarily local, not global. The centralization of investment resources and the formation of elites are interrelated processes. That is why in our research we pay much attention to the processes of emergence and development of central and regional elites. These processes have greatly influenced the deformation of economic structure, disturbances in the process of redistribution of private ownership (the so-called process of 'nomenklatura privatization'), and in investment processes. The clan-corporate structures formed on federal and regional levels prevent Westernized market transformation. It is therefore necessary that the economy reorganizations should be taken simultaneously with the change in the hierarchic structures of political power. For a more even and better targeted distribute of investment resources and to counter spatial-economic imbalances, it is necessary to eliminate the old system of branch and regional clan-corporative structures.
Keywords: 330